Desenvolvimento e aplicação de ferramentas bioinformáticas para a biologia da conservação - Congrains, Karla Verónica Chávez Rodríguez de (Universidade Federal de São Carlos, 2018)
The analysis of demographic and genetic data is recommended for the success of conservation programs. The integration of this information to generate guidelines for establishing self-sustaining populations and retain the greatest amount of genetic diversity is one of the major objectives of ex situ conservation programs. However, the lack of free and easy-to-use programs developed for conservation purposes are rare. The development of high-level programming languages such as Python and R allows researchers, outside the area of computing, to create their own programs. In this work, three computational tools were developed: STRR, PedmineR, and HetRank. These programs aim to assist in studies of biodiversity conservation. They were designed to aid in the analysis of genetic and demographic data. In such a way, STRR evaluates the quality of the panel of microsatellite markers, and brings a filtering makes indications about the possible use of it. PedmineR facilitates the estimation of demographic and genetic parameters based on pedigree data allowing the incorporation of the panel of microsatellite markers. HetRank predicts individual heterozygosity for the offspring of reproductive mates, been a useful tool for captive breeding programs. The use of these tools in the study of the captive population of the golden-faced lion tamarin (Leontopithecus chrysomelas) shows the applicability and easy use of them, having outlined a methodology that can be repeated in the study of other species.
Keywords: Biologia da conservação; Ferramentas bioinformáticas; Microssatélites; Análise de risco; Viabilidade populacional; Conservation biology; Bioinformatic tools; Microsatellites; Hazard risk; Ex situ; Population viability analysis; Biologia de la conservación; Herramientas bioinformáticas; Microsatélites; Análisis de riesgo; Viabilidad poblacional; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL